Comparison of Outcome of Monopolar Diathermy Versus Harmonic Scalpel in Terms of Gallbladder Perforation in Laparoscopic Cholecystectomy - Afifa Asghar,Aamir Ghazanfar, Afifa Asghar,Aamir Ghazanfar (Journal of Rawalpindi Medical College, 2019)
Background : To compare the outcome (in terms of gall bladder perforation) of monopolar diathermy versus harmonic scalpel use during laparoscopic Cholecystectomy (LC) . Methods: In this randomized controlled trial 170 patients of both gender between age 20 to 60 years planned for undergoing laparoscopic cholecystectomy for symptomatic gallstones, were included. Patients were randomly allocated to Group A (harmonic scalpel) and Group B (monopolar diathermy). Outcome was measured in terms of gall bladder perforation during the procedure in both groups. Results: Satisfactory outcome (non-perforated gallbladder) was significantly higher in patients who underwent LC with harmonic scalpel (90.6%, n=77/85) when compared to patients underwent LC with monopolar diathermy (77.6%, n=66/85). P-value found to be 0.021. Conclusion: Use of harmonic scalpel is found to be a better a choice during laparoscopic cholecystectomy in terms of per operative gallbladder perforation as compared to monopolar diathermy.